Więź zewnętrzna rodziny robotniczej rejonu uprzemysławianego w procesie przemian - Tyszka, Zbigniew (Wydział Prawa i Administracji UAM, 1985)
The author surveys the effect of accelerated industrialization and urbanization of a town and its local region on a strength and a character of bonds of families of manufacturing industry workers with the crucial elements of local and regional svstem of social microstructures on the example of changes which took place in the industrialized town of Konin in the years 1967 - 1979. The survey results are the following:1) A long standing industrialization and urbanization of the Konin region did not result in a diminishing of family bonds in working class families with their close kins. It was undoubtedly influenced by the regional deseendence of the working class of Konin, what is typical for the formerly agricultural and presently industrialized regions of Poland (substantial reserves of regional working force). 2) A decrease in a percentage of large (three generational) families wras clearly established in Konin in comparison to stabilized towns and the domestic mean values. It is a typical phenomenon for the intensively industrialized town; a high demand for labor induces bringing it from outside what results in a need of securing housing conditions and in developement of housing projects. In such conditions young married couples find more chances to become independent in the aspect of having on own apartment. 3) Some small, loose and intensively concentrated spaciously neighbourhood circles which initially had developed in the industrialized town became very loose in the examined years reaching often a stage of non-binding acquaintance. It was effected by a rapid developement of a city character of Konin in the industrial, spatial and architectural respect. 4) A conspicious urbanization of workers' families social life could be observed, manifested in becoming independent socially from family and neighbourhood bonds. 5) In the industrialized city, the formalized, external institutional "premises'' of the existence of workers' families (and all employees' families) does not follow the rapid industrial and demographic developement of the city. The obvious conclusions for the social policies can be easily inferred from that situation.
The external bond of a working class family of the industrializeà region in the process of changes